A closer look at private law methodology - Кіріяк; Kiriiak, Оксана; Oksana; Protskiv, Nataliia (Підприємництво, господарство і право, 2021)
The purpose of this article is to substantiate the influence of the methodology of private law on the processes of law-making and law enforcement. Pursuing the goal of presenting broad coverage of the issue, the authors tend towards a narrative style that favors simplicity over generality or rigor. Research methods. The also applied mixed methods in identifying frameworks of private law and their relative visibility striving to allay bias inherent in a single method. Thus, it is distinguished two main branches of the research methods being used in this article: general scientific and special methods of scientific knowledge. Results. The conclusion summarizes the article’s main arguments by suggesting the new definition of term “methodology” through two key meanings: 1) a system of methods and techniques used in a particular field of activity and 2) the doctrine of such a system as general theory of method, theory in action. To put it another way, this article starts where most of previous studies have given up: it has been concluded such main features of the method of regulation of private law relations, as legal equality of participants, free will of the parties, their initiative, property independence, use of dispositive norms. It is noted that the methodology is also based on a system of principles, which are also enshrined in Article 3 of the Civil Code of Ukraine due to the implementation of the rules private international law in national law become, the rules formulated in the Principles, Definitions and Model Rules of Private European Law (DCFR), Principles of European Contract Law (PECL), Principles of European Law (PEL), Principles of European Insurance Law, Principles of Acquis, Principles of UNIDROIT. Conclusions. The results of our empirical analysis provide strong evidence that the interaction between theory and practice in methodology should be the basis of the study, because it is the methodology which solves the problems posed by practice and vice versa, the problems of practice lead to the creation of rational legal constructions.
Keywords: methodology; practice; methods; norms; private law